Poly[(μ(6)-naphthalene-1,4-dicarboxylato-κ(6) O (1):O (1′):O (1′):O (4):O (4′):O (4′))iron(II)] - Boeckmann, Jan (International Union of Crystallography, 2008)
In the title compound, [Fe(C(12)H(6)O(4))](n), the Fe(II) atom is coordinated by six O atoms from six symmetrically equivalent naphthalene-1,4-dicarboxylate ligands in a strongly distorted octahedral geometry. These octahedra are connected via common edges into chains that elongate along the a axis, with Fe⋯Fe distances of 2.9712 (4) and 2.9724 (4) Å. The chains are linked via the naphthalene-1,4-dicarboxylate ligands into a three-dimensional coordination network.